2015
DOI: 10.3389/fnins.2015.00133
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as a method of symptom management in multiple sclerosis

Abstract: Multiple Sclerosis (MS) is an immune-mediated process in which the body's immune system damages myelin in the central nervous system (CNS). The onset of this disorder typically occurs in young adults, and it is more common among women. Currently, there is no cure and the long-term disease progression makes symptomatic management critical for maintaining quality of life. Several pharmacotherapeutic agents are approved for treatment, but many patients seek complementary and alternative interventions. Reviews hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Typically in Multiple Sclerosis several lesions occur at different locations within the CNS with a potential impact on the anatomical systems that are involved in walking and in motor control. The resulting impairments can be relative muscle weakness, sensory deficits, spasticity, and fatigue interfering with different aspects of the walking function such as endurance, muscle coordination, and balance with negative impact on activities of daily living (Cattaneo et al, 2014; Frank and Larimore, 2015; Michailidou et al, 2015). Despite the high prevalence of gait disorder in PwMS, there are relatively few reports describing gait parameters and overall these studies have reported slower walking with shorter stride length and prolonged double support phase, independently of their walking speed (Benedetti et al, 1999; Martin et al, 2006; Givon et al, 2009; Cameron and Wagner, 2011; Kasser et al, 2011; Remelius et al, 2012; Lizrova Preiningerova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Typically in Multiple Sclerosis several lesions occur at different locations within the CNS with a potential impact on the anatomical systems that are involved in walking and in motor control. The resulting impairments can be relative muscle weakness, sensory deficits, spasticity, and fatigue interfering with different aspects of the walking function such as endurance, muscle coordination, and balance with negative impact on activities of daily living (Cattaneo et al, 2014; Frank and Larimore, 2015; Michailidou et al, 2015). Despite the high prevalence of gait disorder in PwMS, there are relatively few reports describing gait parameters and overall these studies have reported slower walking with shorter stride length and prolonged double support phase, independently of their walking speed (Benedetti et al, 1999; Martin et al, 2006; Givon et al, 2009; Cameron and Wagner, 2011; Kasser et al, 2011; Remelius et al, 2012; Lizrova Preiningerova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of Yoga not clear, but it is covered in this review, yoga therapy in luences the level of raised biomarkers such as ACTH and cortisol, which has vital role (Frank and Larimore, 2015).…”
Section: Interaction Of Yoga Therapy On Ms Patientmentioning
confidence: 99%
“…Yoga couples physical exercise through specific movements and poses with mental focus through meditation and breathing to improve posture, flexibility, and strength, and to lower stress and anxiety to provide pain relief. Studies have reported the benefit of Yoga on neck pain, LBP, and multiple sclerosis [47‐49].…”
Section: Pt and Modalitiesmentioning
confidence: 99%